Interactive Project-Based Learning Videos to Improve Student Independence in Economic Activity Material for Grade IV Elementary School - Ni Putu Riasri; Desak Putu Parmiti; Basilius Redan Werang (Universitas Pendidikan Ganesha, 2024)
Low student independence in learning is indicated by student dependence on teachers to understand the material and the lack of use of learning media that support independent learning. The purpose of this study is to develop interactive project-based learning video media to improve student independence in the material of economic activities in grade IV elementary schools. The development model used is ADDIE, which consists of analysis, design, development, implementation, and evaluation. This study involved two material experts and two media experts as validators, as well as teachers and students for practicality trials. Data were collected using a questionnaire with a rating scale instrument. The techniques used in analyzing the data were qualitative descriptive analysis, quantitative statistics, and inferential. The results of the study showed a score of 0.97 from material experts and 0.93 from media experts with very relevant criteria. The practicality test showed a level of practicality of 100% from teachers and 90% from students, with a very practical category. The effectiveness test showed a significant difference between the level of student independence before and after using this learning media. It was concluded that interactive project-based learning video media increased student independence. This study implies that interactive project-based learning videos on economic activity material are developed in the form of digital media. Digital learning media in the form of learning videos can increase students' enthusiasm and passion and can train independence in learning.